Tin-based high-entropy alloy composite brazing filler metal and preparation method thereof

By adding high-entropy alloys to tin-based solder, the problems of insufficient comprehensive performance of lead-free solder and high melting temperature and component segregation during welding are solved, and the low melting point and high mechanical properties of tin-based high-entropy alloy composite solder are realized. Performance, improves welding performance.

CN119188018APending Publication Date: 2024-12-27QIQIHAR UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411285975.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lead-free solder has not yet completely replaced the traditional Sn-Pb solder, and its comprehensive performance is insufficient, and there are problems such as high melting temperature, segregation of components and different structures during the welding process, which affects the welding performance.

Method used

The high-entropy alloy is used as the reinforced phase and added to the tin-based solder. The composite solder is prepared by uniform mixing and pressing processes. The multi-element interaction of the high-entropy alloy is used to improve the wettability and mechanical properties of the solder and inhibit tissue. Semi-revolution and component defects.

Benefits of technology

The low melting point, good wetting and mechanical properties of tin-based high-entropy alloy composite solder are achieved, which solves the problems of high melting temperature and composition segregation during the welding process, and improves welding performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention belongs to the field of composite brazing filler metal, and relates to tin-based high-entropy alloy composite brazing filler metal and a preparation method thereof. The problems that an existing lead-free brazing filler metal is complex in preparation and poor in comprehensive performance are solved. The tin-based high-entropy alloy composite brazing filler metal or composite solder paste is prepared by taking tin-based brazing filler metal as a matrix and high-entropy alloy as a reinforcing phase and adding high-entropy alloy powder with the mass fraction of 0.1-10% into tin-based brazing filler metal powder or solder paste. The tin-based high-entropy alloy composite brazing filler metal is excellent in wettability, mechanical property and the like, the preparation method is simple, the cost is low, the production efficiency is high, and the tin-based high-entropy alloy composite brazing filler metal is mainly suitable for the field of electronic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite materials and relates to a tin-based high-entropy alloy composite brazing filler metal and its preparation method. Background Technology

[0002] The invention and use of solders have a history of thousands of years. Traditional Sn-Pb solders possess excellent electrical and mechanical properties, a suitable melting point, corrosion and oxidation resistance, reliability, high mechanical strength, and good liquid flowability, and are inexpensive to manufacture. Lead, on the other hand, is a toxic metallic element; long-term contact with lead-containing substances can harm human health. With technological advancements and increasing environmental awareness, calls to ban the use of lead-containing substances are growing louder.

[0003] Currently, the main types of lead-free solders developed include Sn-Cu, Sn-Zn, Sn-Bi, Sn-Ag, Sn-Ag-Bi, Sn-Ag-In, and Sn-Ag-Cu alloys. Although research on these solders is relatively mature, no single lead-free solder alloy yet exhibits superior overall performance compared to Sn-Pb solders.

[0004] To research a lead-free solder with comprehensive performance comparable to traditional Sn-Pb solders, two main methods have been developed to improve its performance. One method is alloying, which uses existing Sn-based lead-free solders as a base and adds alloying elements to improve the base solder's performance. Chinese patent CN 102513720A employs this method, adding a certain amount of one or more of Fe, Ni, Y, Ag, Ti, Zr, Hf, and Sb to the tin-based solder. This improves the mechanical properties and corrosion resistance of the tin-based solder alloy, and its performance remains largely stable after remelting. In patent CN 101745752B, silver nanopowder and bismuth powder or a mixture of bismuth and antimony powder or alloy powder are used to enhance bismuth-based lead-free high-temperature solder. This high-temperature lead-free solder can improve the problems of poor electrical and thermal conductivity of Bi-Ag (or Bi-Sb-Ag) alloy solder. It has advantages such as high strength, long service life, good sealing performance, and smooth and bright solder joints during welding and use.

[0005] Another method is particle reinforcement, which involves generating or directly adding second-phase particles into Sn-based solder to prepare composite lead-free solder, thereby improving the solder's performance. Chinese patent CN 107009045B discloses a method of adding graphene-supported nano-sized or micro-sized graphene-supported cerium oxide as a reinforcing agent to Sn-58Bi solder, resulting in a composite solder with 18-44% increased hardness and 5-20% increased shear strength. In patent CN 110315238B, carbon nanotube-reinforced lead-free solder is a green and environmentally friendly component, and carbon nanotube-reinforced lead-free solder has advantages such as high thermal conductivity, excellent welding performance, and excellent mechanical properties.

[0006] This invention utilizes high-entropy alloys as a reinforcing phase. High-entropy alloys exhibit a "cocktail" effect; multi-principal-element alloys contain multiple elements, and the properties expressed by the resulting alloy are the macroscopic comprehensive properties of the interactions among these multiple components. Simultaneously, the high entropy of high-entropy alloys significantly reduces the Gibbs free energy, giving them thermal stability in their microstructure. Therefore, by leveraging the unique properties of high-entropy alloys and adding them as a reinforcing phase to tin-based solders, lead-free solders with excellent overall performance can be obtained. Summary of the Invention

[0007] The purpose of this invention is to provide a tin-based high-entropy alloy composite solder and its preparation method. The high-entropy alloy is added as a reinforcing phase to the tin-based solder, giving it excellent comprehensive properties such as good wettability and mechanical properties. The preparation method is simple, uses environmentally friendly materials, has high production efficiency, and is low in cost.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows:

[0009] This invention provides a tin-based high-entropy alloy composite solder, comprising: a reinforcing phase high-entropy alloy and a tin-based solder matrix; the high-entropy alloy accounts for 0.1-10% of the tin-based solder, and the remainder is tin-based solder.

[0010] The high-entropy alloys include, but are not limited to, AlCoCrFeNi, CoCrFeMnNi, CoCrCuFeNi, etc.

[0011] The tin-based alloys include, but are not limited to, Sn-Cu alloys, Sn-Bi alloys, Sn-Ag alloys, Sn-Ag-Bi alloys, Sn-Ag-In alloys, and Sn-Ag-Cu alloys. The forms of the tin-based alloys include, but are not limited to, powders, blocks, granules, and solder paste.

[0012] This invention provides a method for preparing a tin-based high-entropy alloy composite solder:

[0013] 1. Weighing materials: Weigh the tin-based brazing filler metal and the high-entropy alloy;

[0014] 2. Mixing materials: Tin-based solder and high-entropy alloy are uniformly mixed to obtain a preliminary mixed material;

[0015] 3. Preparation of brazing filler metal: The mixed powder is prepared into a composite brazing filler metal block.

[0016] The composite solder prepared by the method of the present invention specifically includes the following steps:

[0017] Step 1: Weighing Materials: Weigh a certain amount of tin-based solder and high-entropy alloy, wherein the high-entropy alloy accounts for 0.1-10% of the mass of the tin-based solder, and the remainder is tin-based solder; the tin-based solder is in powder form with a particle size of 10-50 μm; the high-entropy alloy is in powder form with a particle size of 5-30 μm;

[0018] Step 2: Mixing Materials: Place the weighed tin-based solder and high-entropy alloy in a metal powder mixer and mix thoroughly. The mixing speed of the metal powder mixer is 35-150 r / min, and the mixing time is 1.5-3 h.

[0019] Step 3: Preparation of brazing filler metal: In an open mold, the mixed material described in Step 2 is pressed under a certain pressure at a certain rate and held for a certain time to obtain a composite material block. The loading rate is 0.2-10 MPa / s, the holding pressure is 1.1-1.5 times the maximum yield strength of the matrix metal, and the holding time is 3-5 min. The obtained composite material block is then processed into powder and pressed repeatedly 3-5 times. The composite material block is processed into powder using one of the following methods: ball milling, grinding, or atomization.

[0020] Furthermore, the present invention also provides a method for preparing a tin-based high-entropy alloy composite solder:

[0021] 1. Weighing materials: Weigh solder paste and high-entropy alloy;

[0022] 2. Mixing materials: Mix the solder paste and high-entropy alloy evenly to obtain composite solder paste.

[0023] The composite solder prepared by the method of the present invention specifically includes the following steps:

[0024] Step 1: Weighing Materials: Weigh a certain amount of solder paste and high-entropy alloy, wherein the high-entropy alloy accounts for 0.1-10% of the alloy composition in the solder paste, and the remainder is solder paste; the alloy composition in the solder paste should account for 85-89%, and the remainder is flux, etc., with a melting point of 200-270℃, a powder size of 25-45μm, and a flux viscosity of 150±20pa.s;

[0025] Step 2: Mixing Materials: Place the weighed solder paste and high-entropy alloy in a solder paste mixer and mix thoroughly to obtain a composite solder paste. The mixing speed of the solder paste mixer is 35-150 r / min, and the mixing time is 1-2 h.

[0026] Furthermore, the present invention also provides a method for preparing a tin-based high-entropy alloy composite solder: a composite solder paste is obtained by uniformly mixing powder with flux. The alloy component in the composite solder paste accounts for 85-89%, with the remainder being flux.

[0027] Furthermore, the present invention is not limited to the above-described preparation method. When the tin-based solder and high-entropy alloy are in block or granular form, preparation methods such as vacuum arc melting and vacuum induction melting can be used.

[0028] Compared with traditional tin-based solders, the advantages of this invention are:

[0029] 1. This invention strengthens tin-based solders with high-entropy alloys. Since high-entropy effect elements such as Sn can have a high concentration in the high-entropy tin-based alloy system without causing the formation of brittle intermetallic compound Cu-Sn phase, it effectively suppresses the occurrence of microstructure segregation and compositional defects in the solder alloy, improves the solder microstructure and enhances the overall performance of the solder.

[0030] 2. The high-entropy effect and slow diffusion effect of the high-entropy alloy in the brazing filler metal of this invention play an important role in inhibiting the excessive dissolution of the alloy base material into the brazing seam during the brazing process, solving the problems of "high melting temperature - compositional segregation - different microstructures" in the preparation process, and its performance surpasses that of traditional tin-based brazing filler metals;

[0031] 3. In the brazing process of the composite brazing alloy in this invention, since the melting point of the SAC eutectic alloy is 217℃, β-Sn and Cu6Sn5 are generated first. Then, the high-entropy alloy will further react with β-Sn, resulting in a slight adjustment of the Sn content, which increases the mass percentage of Ag and Cu, and thus narrows the melting range.

[0032] 4. The present invention has better wettability, lower melting temperature, better wettability, and mechanical properties that surpass those of traditional tin-based brazing fillers, and has a revolutionary effect in the brazing industry. Attached Figure Description

[0033] Figure 1 The thickness of the interface compound (Cu6Sn5 and Cu3Sn) layer after aging at 180°C at the solder joints of tin-based high-entropy alloy composite solders and Cu in Examples 1, 3, and 5 is shown. Detailed Implementation

[0034] The present invention will be described in detail below with reference to specific embodiments. These embodiments can further clarify the present invention, but they are not intended to limit the present invention. Specific Implementation Example 1:

[0036] This embodiment uses a tin-based high-entropy alloy composite solder. The specific mass of each component is shown in Table 1. The high-entropy alloy is Al. 0.1 CoCrFeNi; the tin-based solder is Sn96.5Ag3.0Cu0.5 (SAC305) lead-free solder.

[0037] The preparation method of the tin-based high-entropy solder composite material in this example is as follows:

[0038] Step 1: Weigh SAC305 powder and Al using an electronic balance with an accuracy of 0.0001. 0.1 5g of CoCrFeNi powder; by mass percentage: Al 0.1 The composition of CoCrFeNi powder is 1%, with the remainder being SAC305 powder; the SAC305 powder has a particle size of less than 50 μm; the Al... 0.1 CoCrFeNi powder has a particle size of less than 30 μm.

[0039] Step 2: Weigh the SAC305 and Al obtained in Step 1. 0.1 The CoCrFeNi mixed powder was placed in a beaker and stirred evenly with a glass rod for preliminary mixing. The glass rod was stirred 150-200 times.

[0040] Step 3: Place the mixed powder into an open mold, increase the loading pressure from 0 to 400 MPa, the loading speed is 1 MPa / s, and the holding time after loading is 5 min. After the resulting composite material block is ground into powder, it is repeatedly pressed 3-5 times to obtain the required brazing filler block. Specific Implementation Example 2:

[0042] The main difference between this embodiment and Embodiment 1 is the percentage content of the added high-entropy alloy, as shown in Table 1. The melting point and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 3:

[0044] The main difference between this embodiment and Embodiment 1 is the percentage content of the added high-entropy alloy, as shown in Table 1. The melting point and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 4:

[0046] The main difference between this embodiment and Embodiment 1 is the percentage content of the added high-entropy alloy, as shown in Table 1. The melting point and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 5:

[0048] The main difference between this embodiment and Embodiment 1 is the percentage content of the added high-entropy alloy, as shown in Table 1. The melting point and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 6:

[0050] The main difference between this embodiment and Embodiment 1 is the percentage content of the added high-entropy alloy, as shown in Table 1. The melting point and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 7:

[0052] The main difference between this embodiment and Embodiment 1 is the percentage content of the added high-entropy alloy, as shown in Table 1. The melting point and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 8:

[0054] This embodiment uses a tin-based high-entropy alloy composite solder. The specific mass of each component is shown in Table 1. The high-entropy alloy is Al. 0.1 CoCrFeNi; the tin-based solder is SAC305 solder paste.

[0055] The preparation method of the tin-based high-entropy solder composite material in this example is as follows:

[0056] Step 1: Weigh a certain amount of solder paste and Al0.1CoCrFeNi powder using an electronic balance with an accuracy of 0.0001. The content is expressed as a percentage by mass: Al 0.1 The CoCrFeNi powder accounts for 1% of the alloy content in the solder paste; the solder paste alloy composition is SAC305, melting point 217-225℃, powder size 24-45μm, flux content 11.8±0.5%, viscosity 150±20pa.s; the Al0.1CoCrFeNi powder particle size is less than 30μm;

[0057] Step 2: Weigh the solder paste obtained in Step 1 and Al 0.1 CoCrFeNi powders are mixed and stirred evenly with a stirring blade to obtain a composite solder paste. The stirring blade is used to stir 150-200 times. To further improve the uniformity of the solder paste and the high-entropy alloy, a solder paste mixer can be used to stir the composite solder paste. The stirring speed of the solder paste mixer is 35-150 r / min, and the stirring time is 1-2 h. Specific Implementation Example 9:

[0059] The main difference between this embodiment and Embodiment 8 is the percentage of high-entropy alloy added, as shown in Table 1. The melting temperature and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 10:

[0061] The main difference between this embodiment and Embodiment 8 is the percentage of high-entropy alloy added, as shown in Table 1. The melting temperature and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 11:

[0063] The main difference between this embodiment and Embodiment 8 is the percentage of high-entropy alloy added, as shown in Table 1. The melting temperature and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 12:

[0065] The main difference between this embodiment and Embodiment 8 is the percentage of high-entropy alloy added, as shown in Table 1. The melting temperature and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 13:

[0067] The main difference between this embodiment and Embodiment 8 is the percentage of high-entropy alloy added, as shown in Table 1. The melting temperature and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1. Specific Implementation Example 14:

[0069] The main difference between this embodiment and Embodiment 8 is the percentage of high-entropy alloy added, as shown in Table 1. The melting temperature and wettability of the tin-based high-entropy composite solder in this embodiment are detailed in Table 1.

[0070] The main difference between Specific Embodiments 1 to 7 and Specific Embodiments 8 to 14 lies in the state of the SAC305 solder. The base material used in Embodiments 1 to 7 is SAC305 alloy powder, while the base material used in Embodiments 8 to 14 is SAC305 solder paste.

[0071] Performance testing:

[0072] (1) Melting point test: The composite solder prepared in the example was subjected to performance testing. The testing process is as follows:

[0073] The melting temperature of the composite brazing filler metal was determined using a Photo-DSC 204 F1 differential scanning calorimeter. The filler metal sample was 5 mg, and high-purity nitrogen was used as the protective atmosphere. The melting point was tested at a heating rate of 10 °C / min.

[0074] (2) Wetting test: Referring to standard GB / T 11364-2008, a certain amount of composite brazing filler metal was weighed and placed on a pure copper plate with dimensions of 20×20×1mm. The copper plate was then placed in a resistance furnace and heated to 250℃. The solder was kept at this temperature for 10 minutes to obtain a wetting spread diagram. The spread area of ​​the solder joint was measured using ImageJ software. The spread area of ​​the brazing filler metal was divided by the area of ​​the Cu plate to obtain the spread rate. The average spread rate of 6 samples was taken as the final wetting area of ​​the brazing filler metal.

[0075] Table 1. Composition and properties of composite solders in Examples 1 to 14

[0076] SAC305 matrix Specific Implementation High-entropy alloy content (Wt%) Melting point (°C) Spread coverage (%) powder Example 1 1% 207.6 48.08 powder Example 2 2% 204.1 45.12 powder Example 3 3% 211.1 47.99 powder Example 4 4% 214.7 49.38 powder Example 5 5% 217.6 50.33 powder Example 6 6.5% - 46.87 powder Example 7 9% - 43.65 solder paste Example 8 1% 207.4 48.98 solder paste Example 9 2% 204.9 45.04 solder paste Example 10 3% 210.4 48.27 solder paste Example 11 4% 214.9 49.36 solder paste Example 12 5% 217.5 50.95 solder paste Example 13 6.5% - 46.88 solder paste Example 14 9% - 43.65

[0077] As shown in Table 1, the tin-based high-entropy alloy composite solder of this invention has a melting point of 207.4-217.5℃. The widely used SAC305 solder has a melting point of 217℃, meaning the tin-based high-entropy alloy composite solder has a minimum melting point of 207.4℃, representing a maximum reduction of 9.6℃ compared to the SAC305 alloy. This demonstrates that adding a high-entropy alloy can lower the melting point of the base solder to varying degrees.

[0078] As shown in Table 1, the spreading rate of the tin-based high-entropy alloy composite solder described in this invention ranges from 43.65% to 50.95%. The spreading rate of the widely used SAC305 solder is 43.21%, while the spreading rate of the tin-based high-entropy alloy composite solder can reach a maximum of 50.95%. Compared with SAC305 solder, the spreading rate of the tin-based high-entropy alloy composite solder is increased by up to 7.74%. Therefore, the addition of the high-entropy alloy improves the wettability of the SAC305 alloy.

[0079] Figure 1 The figure shows the thickness of the interface compound (Cu6Sn5 and Cu3Sn) layer at 180°C after soldering the tin-based high-entropy alloy composite solder to Cu. The figure reveals that the thickness of the interface compound layer decreases after adding the high-entropy alloy. Therefore, the tin-based high-entropy alloy composite solder of this invention, with its reinforcing phase high-entropy alloy, can hinder the diffusion of interface elements, effectively suppress the growth of interface compounds, and improve the reliability of the packaged solder joints.

Claims

1. A tin-based high entropy alloy composite solder and a preparation method thereof, wherein the composite solder is characterized in that: The composition includes the following components in terms of mass percentage: 0.1-10wt.% of high entropy alloy and the rest is tin-based solder; the preparation process mainly includes weighing materials, mixing materials and preparing solder.

2. According to claim 1, the high entropy alloy includes but is not limited to AlCoCrFeNi, CoCrFeMnNi, CoCrCuFeNi; the tin-based solder includes but is not limited to Sn-Cu alloy, Sn-Bi alloy, Sn-Ag alloy, Sn-Ag-Bi alloy, Sn-Ag-In alloy, Sn-Ag-Cu alloy, etc.; the shapes of the tin-based solder and high entropy alloy include but are not limited to powder, block, granular, solder paste, etc.

3. A tin-based high entropy alloy composite solder and a preparation method thereof according to claim 1, characterized in that The composite solder block, composite solder paste and the like can be prepared by the preparation process described in claim 1.

4. According to claim 3, a tin-based high entropy alloy composite solder and a preparation method thereof are completed by the following steps: Step 1: weighing materials: weighing a certain amount of tin-based solder powder and high entropy alloy powder; Step 2: Mix the materials obtained in step 1 and stir them evenly to obtain a mixed powder; Step 3: preparing solder: preparing the mixed powder into a composite solder block.

5. A tin-based high entropy alloy composite solder according to claim 3, characterized in that The preparation method of the composite solder paste is completed according to the following steps: Step 1: weighing materials: weighing a certain amount of solder paste and high entropy alloy powder; Step 2: Mixing materials: Evenly mix the materials weighed in step 1 to obtain a composite solder paste.

6. According to claim 4, the particle size of the tin-based solder powder is 10-50 μm; the particle size of the high entropy alloy powder is 5-30 μm.

7. The method for preparing the composite solder according to claim 4, wherein the mixed powder is pressed to prepare a tin-based high entropy alloy composite solder block, characterized in that: In a mold, the mixed powder is pressed at a certain rate to a certain pressure and maintained for a certain time to obtain a composite material block; the loading rate is 0.2-10MPa / s, the holding pressure is 1.1-1.5 times the maximum yield strength of the matrix metal, and the holding time is 3-5min.

8. The preparation method according to claim 4 is not limited to the preparation method according to claim 4, and also includes preparation methods such as vacuum arc melting method, vacuum induction melting method, etc.

9. The tin-based high entropy alloy composite solder and the preparation method thereof according to claim 5 is characterized in that: The composite solder paste is stirred at a stirring speed of 35-150 r / min for 1-2 hours to fully mix the materials.

10. The composite solder paste according to claim 5 is not limited to the preparation method according to claim 5, and further comprises the mixed powder and the flux being uniformly stirred and mixed, and the stirring conditions are the same as those of claim 9.

Citation Information

Cited By

  • Low-temperature self-lubricating high-entropy alloy wire and preparation method and application thereof

    CN122076960A